HUBUNGAN DUKUNGAN KELUARGA DENGAN TINGKAT KECEMASAN PADA LANSIA PENDERITA HIPERTENSI DI POSBINDU WILAYAH PUSKESMAS LANGKAPLANCAR TAHUN 2022 - Poppy, Neng Poppy; Simamora, Rotua Suriany; Ratnah, I (Soscience: Jurnal Ilmu Sosial Science, 2025)
Hypertension is one of the diseases that is often suffered by the elderly due to various changes that are experienced with age. Hypertension control can be done with family support which is an important element for individuals in overcoming health problems but if family support is not provided it can cause anxiety for individuals, because one of the factors of anxiety is the environment, one of which is the family environment. The methods used by researchers are quantitative. The design in this study used analytical observational and used a cross-sectional approach. The sample of this study was the elderly aged 60-90 years who had hypertension in posbindu area of the Langkaplancar Health Center as many as 105 people. The sampling technique in this study used probability technique, using a type of simple random sampling. Bivariate analysis using chi square statistical test. Based on the results of the study, a p-value (0.048) < (0.005) was obtained, which means that there is a significant relationship between family support and anxiety levels in the elderly with hypertension at the Posbindu area of the Langkaplancar Health Center in 2022.